PENERAPAN PERMAINAN LOTTO UNTUK MENINGKATKAN KONSENTRASI BELAJAR PADA ANAK TUNA GANDA (ADHD DAN BIF) DI SDN GROBOGAN 02 KEC. JIWAN KAB. MADIUN - Adam Satriyo Putra Madhani; Prastyo Budiningsih; Febri Tri Marthadiputri; Emilia Julaika; Monika Dyah Arwidiavin Diantri; Dian Agestiningsih; Intan Permatasari; Murtadlo; Endang Pudjiastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the concentration of learning of children with multiple disabilities with ADHD and BIF in Inclusive Schools. This type of research is an experiment with a single subject experiment type or Single Subject Research, A-B-A design, the subject of this study is a child with multiple disabilities (ADHD and BIF) who shows symptoms of being unable to fully focus on objects. In this study, the data collection technique is to use duration to find out how long children are able to focus their attention during a learning session, which lasts for 20 minutes. Data were analyzed using visual graphic techniques.